Implementasi REST API Menggunakan JSON WEB Token (JWT) Pada Sistem Monitoring KPI Berbasis Mobile di PT Industri Kereta API (Persero) - Dewi Asiah Shofiana; Saddam Surya Mardiansyah; M. Iqbal Parabi; Admi Syarif (Jurnal Komputasi, 2024)
In today's competitive and dynamic business environment, modern companies increasingly recognize the importance of Key Performance Indicators (KPIs) for monitoring and ensuring performance. PT Industri Kereta Api (Persero) faces challenges in managing and monitoring numerous KPIs. This research aims to develop a KPI monitoring system using a REST API to handle significant data volumes and ensure relevant and reliable information. Implementing REST API addresses data complexity and ensures efficient operations, providing optimal benefits for the company's management policies. With REST API, the KPI monitoring system can operate across various platforms, such as web and mobile, enhancing information flexibility and accessibility for users. The research focuses on developing an integrated KPI monitoring system, applying REST API for efficient and real-time data access, designing and testing a mobile application, and conducting comprehensive testing. Security testing indicates a good level of system security, performance testing shows the application can handle high loads with stable response times, black box testing demonstrates that the system functions well and meets specifications without significant errors, and user acceptance testing (UAT) achieved a satisfaction index of "Very Satisfactory" with an 88.75% result. This research uses the Personal Extreme Programming (PXP) method, an iterative process suitable for individual software engineers, ensuring flexibility and responsibility in handling changing requirements.